Comparison Of Mimosine Content And Nutritive Values Of Neolamarckia Cadamba And Leucaena Leucocephala With Medicago Sativa As Forage Quality Index - Mohamed, Zaky Zayed; Mohamed Abdallah, Zaki; Fasihuddin Badruddin, Ahmad; Wei-Seng, Ho; Shek-Ling, Pang (IJSTR, 2014)
A study was conducted to determine the mimosine content and the nutritive values of Neolamarckia cadamba and Leucaena leucocephala in comparison to Medicago saliva (alfalfa hay) as forage quality index. A total of 22 N. cadamba and 35 L. leucocephala seedlings were analyzed to determine the mimosine content after 6 months of planting. It was noted that the mimosine content was highest in L. leucocephala (1.6%) and lowest in N. cadamba (0.03%) in comparison to M. sativa which has no mimosine content. Crude protein content was 23.48%, 20.90% and 14.83% for L. leucocephala, N. cadamba and M. sativa, respectively. The crude fiber was maximum in M. sativa (27.23%) and minimum in L. leucocephala (18.77%). Crude protein, crude fat, gross energy, protein to energy (P/E) ratio, organic matter and total ash in N. cadamba was higher compared to M. sativa. L. leucocephala was lower in nitrogen free extract, crude fiber and total ash compared to N. cadamba. Results from this study clearly indicate that N. cadamba has high forage quality and comparable to the traditional L. leucocephala and M. sativa as forage for ruminant and non-ruminants.